Depressive disorders, bad mental health days, and diabetes management behaviors among non-Hispanic American Indian/Alaska Native adults: Findings from the Behavioral Risk Factor Surveillance System. - Kaipeng Wang; Luohua Jiang; Jie Zhu; Spero M Manson (PLoS ONE)
Objective This study examined the association between diagnosis of depressive disorder, the number of bad mental health days per month, and diabetes management behaviors among American Indian/Alaska Native (AI/AN) adults with diabetes. Research design and methods Data were drawn from the Behavioral Risk Factor Surveillance System (2018-2021), including 2,272 self-identified non-Hispanic AI/AN adults diagnosed with non-gestational diabetes. Key variables included a self-reported prior diagnosis of depressive disorder and the number of bad mental health days in the past month. Outcome variables were seven diabetes management behaviors, such as taking a diabetes management class and performing daily foot checks. Statistical analyses included descriptive statistics, chi-squared tests, ANOVA, and logistic regression models. Results Among the participants, 24.8% were diagnosed with depressive disorder, and 19.5% reported at least 14 bad mental health days in the past month. Logistic regression models show that those reporting depressive disorders were significantly less likely to check their feet daily (adjusted odds ratio (AOR) = 0.56, 95% CI: 0.34-0.92). Individuals with at least 14 bad mental health days were significantly less likely to have ever taken a diabetes management class (AOR = 0.59, 95% CI: 0.36-0.99) and check their feet daily (AOR = 0.37, 95% CI: 0.21-0.65) than those reporting no bad mental health days. Conclusions Depressive disorders and frequent bad mental health days were associated with lower odds of diabetes management behaviors among AI/AN adults. These findings suggest that enhancing mental health support within diabetes management programs may help address disparities in diabetes care among AI/AN adults.